1178 Evaluating Optimal Quantity of Chlorhexidine Solution Needed for Application to Umbilical Cord of Neonates in First 10 Days of Life. (October 2012) - Sazawal, S; Nangia, S; Deb, S; Madhesiya, S; Dutta, A; Dhingra, P; Dhingra, U; Ali, SM; Ame, S; Gupta, S; Ahmed, A; Black, R
Abstract : Background: Efficacy studies of application of chlorhexidine on umbilical cord have suggested significant improvement in neonatal outcomes. An important question for new trials and programs however is what should be the quantity used. There are concerns about the increased risk of hypothermia resulting from spillage or over use of any cleansing liquid solution in newborn. In context of a randomized controlled trial evaluating impact of cord cleansing in Africa, on recommendation of DSMB we undertook a pilot study, which aimed to determine the optimal quantity of the intervention solution required for application on umbilical cord of newborn. Methods: Children were enrolled from both community and hospital in Pemba (n=62) and only from Hospitals in Delhi (n=50). Trained Hospital staff/MCH applied the intervention solution from a dropper bottle filled with 10 ml, on the umbilical cord of the baby generously such that it covered umbilical cord and periumbilical area. A study supervisor to maintain consistency supervised the process. After application the unused volume from each of the containers was measured to determine the actual usage. Results: The mean volume of usage did not differ between Pemba and Delhi (4.58±0.8 ml and 4.79±1.88 ml respectively). The quantity of solution used ranged from 3ml to 7.5ml with a median of 4.5ml. Conclusions: The optimal requirement for application was found to be 5 ml. However to be little conservative we recommend use 6 ml to adjust for any spillage and/or any abnormally long cord.